2015
DOI: 10.1057/jit.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

On being ‘Systematic’ in Literature Reviews in IS

Abstract: General guidelines for conducting literature reviews often do not address the question of literature searches and dealing with a potentially large number of identified sources. These issues are specifically addressed by so-called systematic literature reviews (SLRs) that propose a strict protocol for the search and appraisal of literature. Moreover, SLRs are claimed to be a 'standardized method' for literature reviews that is replicable, transparent, objective, unbiased and rigorous, and thus superior to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
245
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(252 citation statements)
references
References 77 publications
0
245
0
7
Order By: Relevance
“…By aggregating literature to answer specific questions, in particular 'what works', systematic reviews tend to perpetuate the paradigm that gives rise to those questions. 38 They are not well suited to questioning the assumptions that led to those questions. Instead we adopted an approach, described by some methodologists as an 'interpretive' or 'critical' review, 39,40 which aims to produce new ideas rather than answer specific questions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By aggregating literature to answer specific questions, in particular 'what works', systematic reviews tend to perpetuate the paradigm that gives rise to those questions. 38 They are not well suited to questioning the assumptions that led to those questions. Instead we adopted an approach, described by some methodologists as an 'interpretive' or 'critical' review, 39,40 which aims to produce new ideas rather than answer specific questions.…”
Section: Resultsmentioning
confidence: 99%
“…A new paradigm will not arise from systematic reviews of research literature. By aggregating literature to answer specific questions, in particular ‘what works’, systematic reviews tend to perpetuate the paradigm that gives rise to those questions . They are not well suited to questioning the assumptions that led to those questions.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews in general "help to identify research problems and gaps and justify the relevance and timeliness of addressing them" [45], while an SLR in particular helps to identify, evaluate, and interpret "all available research relevant to a particular research question, or topic area, or phenomenon of interest" [25]. However, SLRs suffer from certain limitations that make them applicable only under certain conditions: when answering a narrowly defined, summative research question (no "how" or "why" questions) or conducting a bibliometric analysis [4]. Thus, in our case, the SLR is a suitable approach, because our research question is narrow as our focus is on identifying quality factors of self-tracking solutions (not their relationships or possible measurements) and can be answered in a summative form.…”
Section: Methodsmentioning
confidence: 99%
“…These issues have been found, for example, in SRs on choice architecture, climate vulnerability, and food systems . A study on the use of SR to examine research on technology acceptance found that DBS may systematically exclude relevant literature, sometimes even foundational work . Attempts to correct for terminological instability by including all relevant synonyms will often return unworkably large swathes of irrelevant records.…”
Section: Finding the Evidencementioning
confidence: 99%